2015
DOI: 10.14311/ap.2015.55.0347
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Surface Layer of Rolled Bearing Steel

Abstract: Abstract. This paper describes changes observed in bearing steel due to roller burnishing. Hydrostatic roller burnishing was selected as the most suitable method for performing roller burnishing on hardened bearing steel. The hydrostatic roller burnishing operation was applied as an additional operation after standard finishing operations. All tests were performed on samples of 100Cr6 material (EN 10132-4), and changes in the surface layer of the workpiece were then evaluated. Several simulations using finite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…The most significant disadvantage of compound layer creation is their connectivity with changing dimensions of components. Due to changing dimensions, many parts must be finely ground to achieve the initial dimension accuracy [19,20].…”
Section: Resultsmentioning
confidence: 99%
“…The most significant disadvantage of compound layer creation is their connectivity with changing dimensions of components. Due to changing dimensions, many parts must be finely ground to achieve the initial dimension accuracy [19,20].…”
Section: Resultsmentioning
confidence: 99%
“…(a) Rolling [4,5], these studies report the mechanical property and microstructure of cold rolled low and high carbon steel and its work-hardening behavior during the deformation process;…”
Section: Influence Of the Main Technological Variables Of Cyclical Mementioning
confidence: 99%
“…Gharbi et al [33] showed the effect of the ballburnishing force on residual stress on the surface of AISI 1010. Zemčík et al [34] measured the same on EN 10132-4 specimens. Abdulstaar et al [35] showed the fatigue improvement on Al6082 for both shot peening and ball-burnishing with compressive residual stresses up to 0.5 mm below the surface but without describing the directionality of residual stresses and the method used to measure them.…”
Section: Introductionmentioning
confidence: 99%